2017
DOI: 10.1111/jgs.15228
|View full text |Cite
|
Sign up to set email alerts
|

Racial Disparities in Hospice Outcomes: A Race or Hospice‐Level Effect?

Abstract: Racial differences in intensity of care at the end of life are not attributable to hospice-level variation in intensity of care. Differences in patterns of care between black and white hospice enrollees persist within the same hospice.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

2
28
0

Year Published

2019
2019
2024
2024

Publication Types

Select...
8
2

Relationship

0
10

Authors

Journals

citations
Cited by 49 publications
(30 citation statements)
references
References 37 publications
2
28
0
Order By: Relevance
“…Racial and ethnic disparities in utilization were observed in unadjusted tests but not in adjusted models. Although black and Hispanic individuals are less likely to enroll in hospice, disparities may be explained by other sociodemographic factors, such as economic status, geography, and education. These factors warrant additional study to fully understand whether, and how, minority populations are underserved at the end of life.…”
Section: Discussionmentioning
confidence: 99%
“…Racial and ethnic disparities in utilization were observed in unadjusted tests but not in adjusted models. Although black and Hispanic individuals are less likely to enroll in hospice, disparities may be explained by other sociodemographic factors, such as economic status, geography, and education. These factors warrant additional study to fully understand whether, and how, minority populations are underserved at the end of life.…”
Section: Discussionmentioning
confidence: 99%
“…15 Although these results concur with prior studies of general hospice patient populations, 2,5,16 reasons for this disparity are unclear and not linked to hospice-level effects. 37 One explanation is that African American and Hispanic hospice patients receive systematically different care than non-Hispanic whites. However, supplementary analyses revealed no significant racial/ethnic differences in service use among PWD discharged alive.…”
Section: Discussionmentioning
confidence: 99%
“…However, within a particular hospice, Black and Hispanic people receive care that is similar to that of White people (Price, Parast, Haas, Teno, & Elliott, 2017). In contrast, another study found disparities existed between the quality of care for Black and White people within the same hospice setting (Rizzuto & Aldridge, 2018). Barclay et al (2013) found Black people enrolled in hospice were also less likely to die at home compared with White people even when accounting for other socioeconomic factors such as income, location, and education.…”
Section: Discussionmentioning
confidence: 99%